PERKEMBANGAN HOLISTIK: PEMAHAMAN, CIRI, DAN PRINSIP PERUBAHAN BIOLOGI KOGNITIF, SERTA PSIKOSOSIAL - Ainun Jariyah; Mery Kristina Wele; Yulita Erlina Ngama (LPPM Universitas Cipta Mandiri, 2025)
This research is motivated by the need to understand human development holistically, encompassing biological, cognitive, and psychosocial aspects comprehensively. The problem addressed is how the concept of holistic development can explain the characteristics, physical and psychological changes, as well as the fundamental principles governing the developmental process. The focus of the study is to describe the understanding of holistic development, developmental characteristics, changes occurring in biological, cognitive, and psychosocial aspects, and the principles underlying the developmental process. The method used is a qualitative descriptive literature review by examining relevant academic literature and previous research. Key stages of the study include data collection from journals, books, and scientific articles, analysis of concepts and theories of holistic development, and synthesis of findings. The results show that holistic development is a continuous and interconnected process between physical, cognitive, and psychosocial aspects, characterized by orderly and individual changes. The principles of development emphasize differences in developmental rates among individuals, the close relationship between physical and psychological aspects, and the influence of the environment as an important factor. The main conclusion is that understanding development holistically provides a comprehensive picture of the complex and dynamic human growth process, making this approach essential for application in education, caregiving, and human resource development.